Oral health awareness amongst the medical student of Telengana, India - Pattnaik, Snigdha (International Journal Of Community Medicine And Public Health, 2017)
Background: Attractive smile is a sign of good health. Oral health plays an important role in individuals overall health. Majority of systemic diseases have oral manifestations. Methods: The cross sectional study was carried out amongst the medical students of an Medical college by using WHO ORAL SURVEY for adults, with aims and objectives of estimating the prevalence and severity of oral health problem in the study population, understand and analysis various determinants of diseases of oral cavity and to create awareness on oral health. Results: Out of the 250 repondents, 40% of respondent said, the condition of tooth is very good, which is a sign of good oral hygiene. 13% of the participant said they have never visited a dentist.23%of the participants said; they visited the dentist in last 6-12 months. 32% felt it is necessary to visit dentist regularly. Conclusions: Oral diseases have a significant impact on the quality of life of individuals, their participation in society and economic productivity as well as on health systems, making oral diseases a significant public health concern. Pain and discomfort from cavities, can affect the ability of an individual to chew and to obtain adequate nutrition, which, in turn, affects the immune response and the ability to fight disease.